Low temperature grown CuBi2O4 with flower morphology and its composite with CuO nanosheets for photoelectrochemical water splitting - Patil, Rupali; Kelkar, Sarika; Naphadeab, Rounak; Ogale, Satishchandra (Journal of Materials Chemistry A, 2014)
In this work we highlight a peculiar synthesis protocol for the p-type ternary metal oxide system of copper bismuth oxide (CuBi2O4), which yields a highly crystalline spherulitic morphology at a low temperature of 78 degrees C. We associate this growth with the hydrogen bonding effects imparted by the ethanol-water co-solvent system used for the synthesis. We present a detailed growth mechanism by evaluating different synthesis conditions systematically. Furthermore we show that upon the use of the non-stoichiometric (excess copper) precursor mixture under the same experimental conditions the growth of spherulitic CuBi2O4 changes the size and type of the spherulites. Interestingly, careful optimization of the nonstoichiometric synthesis presents a complete impediment to the spherulitic growth and produces a composite of nanorods of CuBi2O4 and nanosheets of CuO. This anisotropic nanocomposite shows an order of magnitude higher surface area as compared to spherulitic CuBi2O4. Since both CuBi2O4 and CuO are visible light absorbing p-type semiconductors, when the synthesized nanocomposite materials are examined as photoelectrochemical (PEC) photocathodes for water splitting, they show a remarkable dependence on the morphology and phase constitution. Almost 13-fold stronger PEC response is observed as the morphology changes from spherulites to nanorods.